Prostate cancer mortality trends in Argentina 1986-2006: an age-period-cohort and joinpoint analysis Tendencias en la mortalidad por cáncer de próstata en Argentina 1986-2006: análisis joinpoint y de edad-período-cohorte - Camila Niclis; Sonia A. Pou; Rubén H. Bengió; Alberto R. Osella; María del Pilar Díaz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to give an overview of the magnitude, variation by age and time trends in the rates of prostate cancer mortality in Córdoba province and in Argentina as a whole from 1986 to 2006. Mortality data were provided by the Córdoba Ministry of Health and the World Health Organization cancer mortality database. Prostate cancer mortality time trends were analyzed using joinpoint analysis and age-period-cohort models. In Argentina prostate cancer age-standardized mortality rates rose by 1% and 3.4% per year from 1986 to 1992 and from 1992 to 1998 respectively. There was a decreasing trend (-1.6%) for Argentina from 1998 and Córdoba (-1.9%) from 1995. Age-period-cohort models for the country and the province showed a strong age effect. In the country there was an increased risk in the 1996-2000 period, whereas there was decreased risk for birth cohorts since 1946, principally in Córdoba. A decreasing trend in prostate cancer mortality was found in Córdoba as well as in Argentina, which might be attributed to the improvement in treatment in this country. El objetivo de este trabajo fue describir la magnitud, la variación por edad y las tendencias temporales de las tasas de mortalidad por cáncer de próstata en la provincia de Córdoba y en Argentina desde 1986 hasta 2006. Se ajustaron modelos joinpoint y de edad-período-cohorte con los datos de mortalidad del Ministerio de Salud de Córdoba y de la Organización Mundial de la Salud. En Argentina las tasas de mortalidad estandarizada por edad aumentaron 1% y 3,4% por año desde 1986 a 1992 y desde 1992 a 1998 respectivamente. Fue estimada una tendencia decreciente (-1.6%) para Argentina desde 1998 y para Córdoba (-1.9%) desde 1995. Los modelos edad-período-cohorte tanto para Córdoba, como para el país, mostraron un marcado efecto de edad. En el país se encontró un incremento del riesgo en el período 1996-2000, mientras que las cohortes de nacimiento a partir de 1946 mostraron un riesgo decreciente, principalmente para Córdoba. Se encontró una disminución en las tasas de mortalidad por cáncer de próstata en Córdoba y en Argentina, lo cual podría atribuirse a mejoras en los tratamientos en el país.